How HTLV-1 may subvert miRNAs for persistence and transformation - Bouzar Amel B; Willems Luc (Retrovirology, 2008)
Abstract Distinct mechanisms are used by viruses to interact with cellular miRNAs. The role of microRNAs in viral replication and persistence ranges from viral-encoded microRNAs to suppressors of RNA interference. Viruses can also exploit cellular miRNAs for influencing cellular metabolism to ensure efficient replication or latency. In particular, two recent studies provide examples of how HTLV-1 may co-opt or subvert cellular miRNAs for persistent replication and oncogenic purposes. The pathways modulated by these described miRNAs are critically involved in apoptosis, proliferation and innate immune response.